2005
DOI: 10.1002/ejoc.200400826
|View full text |Cite
|
Sign up to set email alerts
|

A Diels–Alder Reaction for the Total Synthesis of the Novel Antibiotic Antitumor Agent Mensacarcin

Abstract: The antibiotic mensacarcin (1), which contains nine stereogenic centers and two epoxy functionalities, is a novel antitumor agent that was first isolated from the culture broth of Streptomyces sp. Gö C4/4 found in a soil sample next to the northern cafeteria of the University of Göttingen. For the synthesis of 1 and related structurally simplified analogs, aDiels–Alder reaction of O‐methyljuglone (11) and the tetrasubstituted 1,3‐butadiene 22 was performed to give the cycloadduct rac‐28, which was transformed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…The synthesis of juglone (6) was started from commercially available 1,5-hydroxynaphthalene, which was oxidized with air in the presence of CuCl in the dark to give 6 in 47% yield. 11 Chemical transformations of 6 to 8 was carried out according to the reported methods 12 with some modifications. Oxidative amination of 6 with dimethylamine (2.0 M solution in THF) in toluene at À40°C gave 2-dimethylaminojuglone (7a) and 3-dimethylaminojuglone (7b) in 42% and 11% yields, respectively.…”
Section: Chemistrymentioning
confidence: 99%
“…The synthesis of juglone (6) was started from commercially available 1,5-hydroxynaphthalene, which was oxidized with air in the presence of CuCl in the dark to give 6 in 47% yield. 11 Chemical transformations of 6 to 8 was carried out according to the reported methods 12 with some modifications. Oxidative amination of 6 with dimethylamine (2.0 M solution in THF) in toluene at À40°C gave 2-dimethylaminojuglone (7a) and 3-dimethylaminojuglone (7b) in 42% and 11% yields, respectively.…”
Section: Chemistrymentioning
confidence: 99%
“…Modifications carried out at position 5 of the naphthoquinone backbone were made using the corresponding side‐chain and silver(I) oxide. Derivatives 16 – 19 and 21 were synthesized according to the methodology described by O'Keefe et al and derivative 20 was prepared according to the procedure reported by Tietze et al with some modifications, as described above. These compounds were obtained in moderate‐high yield (24–83%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…with some variations (Fig. ) . Silver(I) oxide and the corresponding alkyl iodide were added in a slight excess (1.3 equiv.)…”
Section: Resultsmentioning
confidence: 99%
“…Ten compounds were prepared by modifying the 5‐position of the naphthoquinone moiety. These compounds were synthesized according to a literature procedure with some modifications . The corresponding alkyl iodide (0.765 mmol, 1.3 equiv.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation